Kigelia africana (Lam.) Benth leaf extract inhibits rat brain and liver mitochondrial membrane permeability transition pore opening. (4th July 2022) - Falode, John Adeolu; Akinmoladun, Afolabi Clement; Olaleye, Mary Tolulope; Akindahunsi, Afolabi Akintunde
Abstract: The effect of Kigelia africana on mitochondrial membrane permeability transition has not been explored. In this study, the effect of a solvent fraction of Kigelia africana leaf extract on mitochondrial membrane permeability transition of rat brain and liver was evaluated. A methanol extract of K. africana leaves was fractionated into different solvents by vacuum liquid chromatography and following preliminary screening, the dichloromethane:ethylacetate (1:1) fraction was selected for further assays. Constituent phytochemicals in the fraction were revealed by thin-layer chromatography and further purification was carried out to characterize the compounds. Brain and liver mitochondria were isolated and used for mitochondrial membrane permeability transition and adenosine triphosphatase assays. Exogenous Ca 2+ and Al 3+ were used to trigger the mitochondrial membrane permeability transition opening. Physicochemical properties revealed by thin-layer chromatography showed that the isolated compounds were flavonoids. The extract inhibited mitochondrial membrane permeability transition opening in the presence and absence of triggering agents in brain and liver mitochondria. It also inhibited mitochondrial lipid peroxidation and adenosine triphosphatase activity. These results suggest that the extract can limit the rate of apoptosis via inhibition of mitochondrial membrane permeability transition which is pivotal to the mitochondrial apoptotic pathway and is an important therapeutic target in some pathological conditions. Graphical Abstract: UF0001